S128 Baseline characteristics of patients with asthma treated with dupilumab in a real-world setting: results from the RAPID registry. (11th November 2022) - Lugogo, NL; Soler, X; Menzies-Gow, A; Peters, AT; Cote, A; Hilberg, O; Xia, C; Rimington, T; Zhang, Y; de Prado Gomez, L; Rowe, PJ; Radwan, A; et al.
Abstract : Background: Up to 58% of patients with severe asthma still have uncontrolled symptoms, despite receiving recommended treatment. Dupilumab is a human monoclonal antibody that blocks interleukin (IL)-4 and IL-13, key and central drivers of type 2 inflammation. In phase 3 QUEST (NCT02414854 ), add-on dupilumab vs placebo significantly reduced exacerbations and improved pre-bronchodilator (pre-BD) forced expiratory volume in 1 second (FEV1 ) in patients with uncontrolled, moderate-to-severe asthma and elevated type 2 biomarkers (baseline blood eosinophils or fractional exhaled nitric oxide [FeNO]). Dupilumab was generally well tolerated. RAPID (NCT04287621 ) is a global, prospective registry aimed at characterizing patients with asthma initiating dupilumab therapy in real-world clinical practice, including demographics, asthma control, lung function, and disease severity. We report baseline characteristics of patients enrolled during the first 6 months. Methods: The RAPID registry enrols patients aged ≥12 years who initiate dupilumab treatment for the primary indication of asthma according to country-specific prescribing information. Signed consent was obtained (for minors, from parent or legal guardian). Results: During the first 6 months, 205 patients were enrolled. Baseline characteristics included: mean age 50.10 years (±17.41); female (65.4%); body mass index 30.67 (±7.96); 74.1% were White (including individuals of Hispanic origin) and 13.2% were Black or African-American ( table 1 ). 86.8% had moderate-to-severe disease – according to GINA steps 3 to 5, while 6.3% were GINA 1/2. 24.4% were current or former smokers. Patients had 4.10 (±6.30) severe asthma exacerbations in the previous year. Baseline lung function was: pre-BD FEV1, 2.29 L (±1.14) and pre-BD percent predicted FEV1, 70.34% (±20.30). The 6-item Asthma Control Questionnaire score was 2.40 (±1.18) and Asthma Quality-of-Life Questionnaire score was 4.10 (±1.31). In the year before enrolment, 9.3% and 18.5% of patients were hospitalized or visited the emergency room due to asthma, respectively. FeNO was 42.2 ppb (±34.83). Conclusions: In this initial sample from the RAPID study, patients prior to initiating dupilumab had uncontrolled asthma and some had a history of smoking. Patients had a high number of exacerbations in the past year, impaired lung function, and poor asthma control and quality of life, suggesting a population with a high disease burden despite standard-of-care treatment. Please refer to page A212 for declarations of interest related to this abstract.